Penguatan Kompetensi Digital Guru SD melalui Pembelajaran Mendalam dan Smart Learning Berbasis Kemitraan di Kota Sungai Penuh - Ikhsan Ikhsan; Ketut Budiastra; Suhartono Suhartono; Mudayat Mudayat; Eval Setiawan; Elsa Safitri (WISE Pendidikan Indonesia, 2026)
This community engagement program aimed to strengthen the digital capacity of elementary school teachers in Sungai Penuh City, Jambi, through the integration of deep learning as a pedagogical approach and smart learning as a technology-supported learning ecosystem. The program was implemented as a follow-up to the institutional collaboration between Universitas Terbuka and the Sungai Penuh City Government and involved 30 elementary school teachers selected by the local Education Office. A needs-based capacity-building design was employed through field assessment, face-to-face training, technology demonstrations, problem-based practice, interactive discussion, and planned online mentoring. The training introduced learning management systems, artificial intelligence, three-dimensional video, 360-degree cameras, virtual reality, and augmented reality, while emphasizing their alignment with instructional objectives, differentiated learning, and local school conditions. The results indicated active participant engagement and initial capacity development in distinguishing pedagogical deep learning from computational deep learning, identifying appropriate digital tools, connecting technology with differentiated instruction, and designing context-sensitive learning alternatives. The program also revealed major implementation challenges, including limited infrastructure, uneven internet access, and parental misconceptions regarding digital learning. However, these constraints could be partially addressed through low-cost contextual media, institutional collaboration, professional online forums, and peer dissemination. Because the program did not employ validated competency instruments, pretest-posttest measurements, a comparison group, or classroom observations, the findings should be interpreted as implementation evidence and indications of initial capacity development rather than causal proof of improved digital competence. These findings imply that sustainable teacher digital development requires continuous mentoring, product-based assessment, classroom implementation, institutional support, and longitudinal evaluation.